(untitled) (Journal of the College of Basic Education, 2023)
The aim of the current research is to know the habits of the mind and their importance for teachers of the Arabic language. To achieve this, the researcher prepared a list of habits of the mind whose validity was verified by presenting them to a group of experts and arbitrators in the field of curricula, teaching methods, educational psychology, measurement and evaluation, and it consisted in its final form of (16) main habits It is (perseverance, striving for accuracy, collecting data using all senses, thinking and communicating clearly and accurately, applying previous knowledge to new situations, questioning and raising problems, controlling impulsiveness, finding humor, taking responsible risks, listening with understanding and empathy, and being willing to learn continuously. Responding with astonishment and awe, creativity - perception - innovation, thinking about thinking (extracognitive), reciprocal thinking, thinking flexibly). Extracting the psychometric characteristics of it represented by honesty and stability, as the researcher extracted honesty in two ways: (apparent honesty and constructive honesty